Internet Addiction And Aggressive Behavior Among Middle School Students - Zerriouh Nabahet ,Saliha; Chekraoui Abdelkader, Fathia (University of Eloued جامعة الوادي, 2024)
The current study aims to reveal the nature of the relationship between internet addiction and aggressive behavior on a sample of middle school students in Sidi Bel Abbes. The sample included fourth-grade middle school students. We also aimed to identify the differences in internet addiction and aggressive behavior in the sample according to gender. We used a descriptive analytical approach and used both an instrument to measure internet addiction and another to measure aggressive behavior and applied them to a sample of 98 boys and girls from fourth-grade middle school students. The study yielded the following findings: There is a strong positive correlation between internet addiction and aggressive behavior among fourth-grade middle school students. There are no statistically significant differences in internet addiction among fourth-grade middle school students due to gender. There are no statistically significant differences in aggressive behavior among fourth-grade middle school students due to gender.
Keywords: Internet addiction; Aggressive behavior; Middle school students